Photonic Imaging with Optical Coherence Tomography for Quality Monitoring in the Poultry Industry: a Preliminary Study - M Sabuncu; M Akdoğan (Brazilian Journal of Poultry Science, 2015)
ABSTRACTA photonic imaging method that gives the possibility to measure egg quality was applied. Since the method is non-contact and non-destructive we believe that this photonic imaging method may be successfully integrated in the automated inspection systems in the poultry industry. The method involves scanning an invisible infrared light beam over the eggshell, allowing to detect possible cracks and reveal information about the structure of the eggshell. The high resolution, high quality measurements obtained through optical coherence tomography (OCT) make it feasible to be utilized as part of an automated inspection system. In this paper we present an OCT scan image of the egg tip and reconstructed volumetric images of the eggshell surface. The method enables the detection of small cracks on eggs and reveals the detailed inner structures of the cracks.